Comparison of Histological, Clinical, and Radiographic Outcomes of Postextraction Ridge Preservation by Allogenic Bone Grafting With and Without Injectable Platelet-Rich Fibrin: A Double-Blinded Randomized Controlled Clinical Trial - Mohammad Reza Talebi Ardakani; Zeinab Rezaei Esfahrood; Fatemeh Mashhadiabbas; Masoud Hatami (International Journal of Dentistry)
Conclusion: Despite the optimal outcome of ridge preservation in both groups, the application of allograft plus I-PRF yielded superior histological, clinical, and radiographic results compared with allograft alone, and this difference was significant in most variables.